2021
DOI: 10.3389/fpsyg.2021.647681
|View full text |Cite
|
Sign up to set email alerts
|

Technology: Saving and Enriching Life During COVID-19

Abstract: The pandemic of COVID-19 has arrested the life of 7.8 million people living on this earth. However, some people are more vulnerable to the risk of this deadly virus. The frailty of senior citizens put them at the top of this list. The past 6 months have not only presented a threat to their physical health but to mental health also. Although lockdown was necessary to check the spread of the coronavirus it culminated in an exponential rise in the problems of loneliness, anxiety, fear, helplessness, and depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The connections between pandemic, payments and technology is more and more visible, especially that the COVID-19 pandemic has already been perceived as the accelerator of the digital transformation [29,30]. ICT, instant messaging included, FinTech solutions and all kinds of new technologies are perceived as more useful and necessary for everyday activity [57]. Because of the pandemic people have started to use more technologies and digital solutions that were relatively or objectively new in the market (like for example a growing number of EFT-POS in Poland, which are not a new technology, but has given a possibility to pay cashless in the new way for many consumers).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The connections between pandemic, payments and technology is more and more visible, especially that the COVID-19 pandemic has already been perceived as the accelerator of the digital transformation [29,30]. ICT, instant messaging included, FinTech solutions and all kinds of new technologies are perceived as more useful and necessary for everyday activity [57]. Because of the pandemic people have started to use more technologies and digital solutions that were relatively or objectively new in the market (like for example a growing number of EFT-POS in Poland, which are not a new technology, but has given a possibility to pay cashless in the new way for many consumers).…”
Section: Methodsmentioning
confidence: 99%
“…The ICT is a vast area, however especially a use of instant messaging services during the pandemic, such as Whatsapp and Skype, as Sinha at al. shows [57] has significantly mitigated some of the negative effects of restrictions imposed by governments in connection with the pandemic. Not only did it help to maintain social distance and strained interpersonal relationships, but it was also used in many new institutional, formal contexts like remote firms' management, remote learning, or medical advice [58,59].…”
Section: Literature Review-payment Behavior During the Covid-19 Pandemicmentioning
confidence: 99%
“…Another study [12] centered in the Portland-Vancouver-Hillsboro Oregon-Washington Metro Area found that the elderly and retired participants show increased openness to home deliveries in the pandemic, however, it is found that they are less likely to use online shopping compared to the rest of the general population. This supports the high reluctance levels found in [11]. A study by Erjavec and Manfreda [13] studied older adults and concluded that the pandemic caused the rapid adoption of digital solutions such as online shopping due to the disruption of consumers' daily lives.…”
Section: Changes Due To Online Shoppingmentioning
confidence: 62%
“…In adults of more mature ages, it is found that they are more reluctant to adopt online shopping, as for them, there is a steep learning curve and adapting may be difficult for them. This is supported by a study by Sinha et al [11] which found that the elderly's most common problem in the adoption of technologies was a proper support system. Although the pandemic has driven them away from conventional methods, it is found that older adults find it easier to shop online [11].…”
Section: Changes Due To Online Shoppingmentioning
confidence: 63%
See 1 more Smart Citation